2019
DOI: 10.1177/1756287219875581
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of surgical management with an adjustable sling versus an artificial urinary sphincter in patients with severe urinary postprostatectomy incontinence: a systematic review and network meta-analysis

Abstract: Background: The purpose of this study was to determine the effectiveness of an adjustable sling compared with an artificial urinary sphincter (AUS) in patients with severe urinary incontinence (SUI) postprostatectomy (PP). Methods: This review was carried out following the Cochrane Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) declaration. We searched Medline, Embase, LILACS, and CENTRAL databases. Studies with patients older than 18 years of age with SUI PP who underwent sling or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…It is frustrating that the study only compared the efficacy of both interventions before and after surgery and found that the two procedures contributed to decreased daily pad use and quality of life improvement. Guachetá Bomba PL determined the effectiveness of adjustable slings vs. AUS in patients with severe postprostatectomy SUI, despite the fact that he could only conduct a network meta-analysis to compare the two interventions indirectly ( 16 ). He concluded that both were able to reduce incontinence and improve life quality; however, the difference of effectiveness for adjustable slings vs. AUS was not significant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is frustrating that the study only compared the efficacy of both interventions before and after surgery and found that the two procedures contributed to decreased daily pad use and quality of life improvement. Guachetá Bomba PL determined the effectiveness of adjustable slings vs. AUS in patients with severe postprostatectomy SUI, despite the fact that he could only conduct a network meta-analysis to compare the two interventions indirectly ( 16 ). He concluded that both were able to reduce incontinence and improve life quality; however, the difference of effectiveness for adjustable slings vs. AUS was not significant.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, researches on meta-analysis is urgently needed to integrate the existing evidence to draw a conclusion about the preference of two SUI treatments mentioned above. Nevertheless, it is regrettable that recent systematic reviews merely include network meta-analysis that indirectly compares AUS intervention or adjustable slings procedure with non-intervention group ( 16 ), or includes meta-analysis that compares the pad use per day before and after SUI surgery ( 17 ). Moreover, they did not pay attention to moderate male SUI, whose treatment seems to be a choice between AUS and slings.…”
Section: Introductionmentioning
confidence: 99%
“…Treatment for PPUI can be either noninvasive or invasive 24 . Noninvasive approaches include lifestyle management, pelvic floor muscle exercise, and medical treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Noninvasive approaches include lifestyle management, pelvic floor muscle exercise, and medical treatment. The invasive approaches include surgical treatment such as injection of urethral bulking agents, artificial urethral sphincter (AUS) insertion, and adjustable or nonadjustable sling 24 . The goals of surgical treatment for PPUI are to preserve bladder capacity and compliance, improve urethral strength, and reduce urinary leakage; the choice of treatment depends on the severity, duration, and type of symptoms 24 , 25 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation